TAWURAN LINTAS PELAJAR DI TINJAU DARI KRIMINOLOGI - Sansabila Ivana Putri; Made Warka (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
This study aims to identify and explain criminal responsibility for perpetrators of student brawls and to analyze compliance with laws and regulations and criminology using sociological studies. The results obtained from this study are the existence of punishment as regulated in the Criminal Code. The consideration used is the existence of the perpetrator's actions which clearly violate the norms of decency. The actions taken by the perpetrators were carried out consciously and knowing the impact of their actions and those related to child protection